Answer:
-3
Step-by-step explanation:
-x^2 +x–1
Let x = -1
- (-1)^2 + (-1) -1
- 1 -1 -1
-3
Answer:
0
Step-by-step explanation:
the equation after plugging in "x" is
-(-1)*(2)+(-1)-1
then after multiplication it is
2-1-1
this becomes 0
-2 1/8
-1 3/8
1 3/8
2 1/8
Answer: - 2 1/8
Step-by-step explanation: Lets first get common denominators of 8.
-7/4 = -14/8 (-7 x 2 = -14 and 4 x 2 = 8)
-14/8 - 3/8 = -17/8 or -2 1/8
Answer:
2 1/8.
Step-by-step explanation:
That is |-7/4| + 3/8
= 7/4 + 3/8
= `14/8 + 3/8
= 17/8
= 2 1/8.
B. 19.6 square feet
C. 42.8 square feet
D. 78.6 square feet
Answer:
I did the test the answer is 19.6 square feet
Step-by-step explanation:
Answer:
10 :D
Step-by-step explanation:
A.
18 mL
B.
72 mL
C.
60 mL
D.
216 mL
...................................................
the lenth width and heidth are 6cm